PENGUATAN JIWA WIRAUSAHA SYARIAH PADA GENERASI MUDA MUSLIM - Muhammad Rafli; Rachma Febriyanti; Supriadi; Mukhtar Lutfi (JSE: Jurnal Sharia Economica, 2026)
The increasingly competitive global economy highlights the importance of strengthening entrepreneurial spirit among young generations, particularly entrepreneurship based on Islamic values. In the field of Islamic economics, sharia entrepreneurship is not only focused on economic profit but also emphasizes ethical values, social responsibility, and public benefit. This study aims to analyze the strengthening of sharia entrepreneurial spirit among Muslim youth through Islamic values, entrepreneurial competence development, business innovation, and supporting factors for sustainable enterprises. This research employed a literature review method with a descriptive qualitative approach. The research data consisted of secondary data obtained through documentation studies of ten scientific articles relevant to youth sharia entrepreneurship. Data analysis was conducted using content analysis by identifying, categorizing, and synthesizing previous research findings. The results indicate that strengthening sharia entrepreneurial spirit requires integration between Islamic values, entrepreneurial literacy, digital innovation capabilities, and a supportive business ecosystem. This study contributes to understanding the importance of developing Muslim entrepreneurs who are not only economically competitive but also guided by ethical principles and social responsibility. The findings highlight the significance of developing sharia entrepreneurship programs to encourage young Muslims to become innovative, independent, and socially responsible entrepreneurs.